2007
DOI: 10.1074/jbc.m605333200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Ball-and-chain Transport of Ferric Enterobactin through FepA

Abstract: The Escherichia coli iron transporter, FepA, has a globular N terminus that resides within a transmembrane ␤-barrel formed by its C terminus. We engineered 25 cysteine substitution mutations at different locations in FepA and modified their sulfhydryl side chains with fluorescein maleimide in live cells. The reactivity of the Cys residues changed, sometimes dramatically, during the transport of ferric enterobactin, the natural ligand of FepA. Patterns of Cys susceptibility reflected energy-and TonB-dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 59 publications
4
107
2
Order By: Relevance
“…Obvious pathways for transport of ligands are not apparent, raising the question of whether the globular domain exits the b-barrel during ligand transport or colicin translocation. It was predicted (Vakharia and Postle, 2002) and subsequently demonstrated that, when expressed as individual peptides, the globular domain and the b-barrel were capable of restoring transport through interprotein complementation Ma et al, 2007). These data suggested that the internal Fig.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Obvious pathways for transport of ligands are not apparent, raising the question of whether the globular domain exits the b-barrel during ligand transport or colicin translocation. It was predicted (Vakharia and Postle, 2002) and subsequently demonstrated that, when expressed as individual peptides, the globular domain and the b-barrel were capable of restoring transport through interprotein complementation Ma et al, 2007). These data suggested that the internal Fig.…”
Section: Discussionmentioning
confidence: 86%
“…When tethered near the amino-terminal end of the globular domain by disulphides between the amino-terminus and the barrel wall, the TonB-dependent transporters FepA and FhuA were inactive Ma et al, 2007). In the case of FhuA, the addition of reducing agent dithiothreitol restored transport in vivo .…”
Section: Results In the Context Of Previous Studiesmentioning
confidence: 94%
See 3 more Smart Citations